Industrial Wastewater Treatment with Advanced Chemical Methods: A Systematic Review of Trends and Challenges (2020-2025) - Echevarria Perez, Jheyson Aldair; Arroyo Camacuari, Cristhian Anyelo; Cuevas Tenorio, Luis Enrique; Coaquira Torres, Edgar (LACCEI, 2025)
This systematic review analyzes advanced chemical methods for industrial wastewater treatment, focusing on their efficiency, operating conditions and sectoral applications. Applying the PRISMA methodology and the PICO scheme, recent studies (2020-2025) were evaluated showing the superiority of hybrid systems. Combined processes such as electro-Fenton + UV achieved up to 100% pollutant removal in the textile industry, while Fenton + electrocoagulation showed efficiencies of 98.5% in COD. Oxidation with thermally activated persulfate exceeded 79% efficiency for recalcitrant compounds. The results highlight that integrated technologies consistently outperform unitary treatments, offering more effective solutions for complex industrial effluents.